تفعيل دور مهنة المحاسبة في إعداد دراسات الجدوي الاقتصادية للمشاريع الاستثمارية - الإبراهيمي، وحيد محمود رمو (جامعة الموصل - كلية الإدارة والاقتصاد, 2013)
إن أحد أسباب فشل الكثير من المشاريع الاستثمارية في العديد من الدول النامية يعود إلى عدم اعتماد إقامة تلك المشاريع على الدراسة والتحليل والمفاضلة فيما بينها، لأن قيام مثل هذه المشروعات الفاشلة يعني المزيد من إهدار للموارد التي تكون الدول في أمس الحاجة لها، من هنا فإن عملية المفاضلة بين المشاريع يمكن أن تكون بمثابة وسيلة لتحقيق الاستخدام الأمثل للموارد المتاحة. حددت مشكلة البحث من خلال المشكلات التي تعاني منها عملية المفاضلة بين المشاريع الاستثمارية في العراق . وقد هدف البحث إلى إبراز أهمية إعداد دراسات الجدوى الاقتصادية ومنافعها وبيان أهمية تقنيات المعلومات الحديثة في ترصين وشمول دراسات الجدوى الاقتصادية، فضلا عًن تحديد لأطر المسؤولية القانونية والمهنية المحاسبية والتدقيقية عند فشل مشاريع استثمارية سبق إعداد دراسات جدوى اقتصادية لها، وتتضح أهمية البحث خصوصاً في البلدان النامية التي يتوجب عليها الاهتمام أكثر بموضوعات ومجالات وأدوات الاستثمار الأكثر مواءمة ونفع لهذه المجتمعات وبشكل علمي وعملي من خلال التحسين من كفاءة هذه الاستثمارات. وقد توصل الباحث إلى أهمية اعتماد عدة طرائق عند المفاضلة بين مشاريع الاستثمار وعدم الاكتفاء ببعض الطرائق كأن تكون إحداها بديلاً عن الأخرى وإنما التعامل معها لغرض توفير صورة متكاملة عن المشروع. فضلاً عن أهمية إدخال دراسة الجدوى الاجتماعية والبيئية عند إعداد دراسات الجدوى الاقتصادية في العراق. واعتماد البرنامج المقترح في إعداد دراسات الجدوى الاقتصادية نظرا للمزايا العديدة التي يوفرها استخدامه. One of the reasons of the failure by many investment projects in several developing countries is due to the failure to adopt a such projects on the study, analysis and trade-offs among them, because to do such projects failed means more waste of resources to which States are in dire need of them, so the process differentiation Among the projects could serve as a way to optimize the use of available resources. Research problem is identified by the problems faced by the trade-off between investment projects in Iraq. The objective of this research to highlight the importance of preparing feasibility studies and benefits and demonstrate the importance of modern information technology in cemented and comprehensiveness of economic feasibility studies, as well as identifying the frameworks liability and professional accounting and auditing at the failure of investment projects already preparing feasibility studies them, and clear the importance of research, especially in developing countries that they must pay more attention to the themes and areas of investment tools most adapted and benefit to these communities and in a scientific and practical through optimization of the efficiency of these investments. The researcher reached to the importance of adopting a number of ways when the trade-off between investment projects and not just in some ways one of which was a substitute for other, but to deal with it for the purpose of providing a comprehensive picture of the project. As well as the importance of social enter the feasibility study and environmental preparing feasibility studies in Iraq. The adoption of the proposed program in the preparation of feasibility studies due to the many advantages offered by the use.
Keywords: التنمية الاقتصادية -- دراسة الجدوي الاقتصادية -- المشاريع الاستثمارية -- المحاسبة -- النظام المحاسبي -- الموازنة الرأسمالية -- الجوانب الاجتماعية